ANALISIS ASUHAN KEPERAWATAN PADA PASIEN GANGGUAN PERSEPSI SENSORI HALUSINASI PENDENGARAN MELALUI INTERVENSI INOVASI ACEPTANCE AND COMMITMENT THERAPHY (ACT) DI RS JIWA DR. SOEHARTO HEERDJAN, JAKARTA - Nada Tasya Anggini (2023)
Schizophrenic patients with impaired sensory perception: persistent auditory hallucinations can cause disruption to life. Acceptance and Commitment Therapy (ACT) is the newest generation of behavioral therapy that focuses on accepting hallucinations and committing to maintaining good behavior and more value. Aim: the application of this care is to determine the effect of applying ACT on auditory hallucinations in schizophrenic patients. Method: 4 sessions of ACT therapy with 30 minutes of practice. Tools: Patients were evaluated using the Psychotic Symptom Rating Scale (PSYRATS) questionnaire with 11 questions and a total score of 44. Result : There was a significant change in the patient's hallucinations, namely before the intervention was given the symptoms were severe and after being given the intervention the client's symptoms became mild and reduced Recommendations: ACT should be integrated into psychiatric care and interventions, including hospitalized schizophrenic patients who experience auditory hallucinations.